CUSTOMER SATISFACTION AND SWITCHING BARRIER AFFECT CUSTOMER LOYALTY OF PREPAID CARD USERS IN THE TELECOMMUNICATION SECTOR IN SAMARINDA - Tanzil, Fey Fey; Noor, Lorine Kalista (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
The development of technology and the high of globalization, bring change to many people in the world. The rapid development of information technology has made telecommunication necessary. Communication service operators, such as the Mobile Telecommunication Sector that serves cellular telecommunications networks, always try to provide the best service so that people feel satisfied and become loyal to these communication services. This study aims to detect and analyze the effects of customer satisfaction and switching barrier on customer loyalty. Quantitative models are used in this study. Quoting sample used is Purposive Sampling with total of 100 customers of prepaid mobile telecommunication in Samarinda. The pattern of data accumulation is by questionnaire method and data analysis method by multiple linear regression analysis. To determine customer loyalty (customer loyalty) can be measured by variable of customer satisfaction and switching barriers.